2019
DOI: 10.3390/su11247107
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Trace Mineral Level and Source Affect Fecal Bacterial Mineral Incorporation and Mineral Leaching Potential of Equine Feces

Abstract: Minerals excreted in feces have the potential to leach or runoff to water-ways, negatively impacting water quality. This study examined the effect of dietary trace mineral levels, and their source, on the leaching potential of minerals from equine feces. Nine horses were used in a replicated 3 × 3 Latin Square, with three dietary treatments provided as pellets: no added trace minerals (CON), added inorganic trace minerals (ING), and added organic trace minerals (ORG). Supplemental trace minerals included Co, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Additionally, DM disappearance was not different among treatments, so Zn should be equally concentrated in the compost treatments due to similar DM losses. Due to the decrease in organic matter content, concentrations of all minerals were greater in the compost compared to the pre-composted feces, which were reported in another study [18]. Briefly, feces from horses supplemented with trace minerals (ING and ORG) had significantly greater concentrations of Cu and Zn, and tended to have greater concentrations of Co compared to CON [18].…”
Section: Mineral Content Of Compostmentioning
confidence: 60%
See 4 more Smart Citations
“…Additionally, DM disappearance was not different among treatments, so Zn should be equally concentrated in the compost treatments due to similar DM losses. Due to the decrease in organic matter content, concentrations of all minerals were greater in the compost compared to the pre-composted feces, which were reported in another study [18]. Briefly, feces from horses supplemented with trace minerals (ING and ORG) had significantly greater concentrations of Cu and Zn, and tended to have greater concentrations of Co compared to CON [18].…”
Section: Mineral Content Of Compostmentioning
confidence: 60%
“…Due to the decrease in organic matter content, concentrations of all minerals were greater in the compost compared to the pre-composted feces, which were reported in another study [18]. Briefly, feces from horses supplemented with trace minerals (ING and ORG) had significantly greater concentrations of Cu and Zn, and tended to have greater concentrations of Co compared to CON [18]. Other studies have also reported an increase in mineral concentration after composting [6].…”
Section: Mineral Content Of Compostmentioning
confidence: 66%
See 3 more Smart Citations